Arabidopsis Type III Gγ Protein AGG3 Is a Positive Regulator of Yield and Stress Responses in the Model Monocot Setaria viridis - Kaur, Jagdeep; Roy Choudhury, Swarup; Vijayakumar, Anitha; Hovis, Laryssa; Rhodes, Zach; Polzin, Rob; Blumenthal, Dylan; Pandey, Sona (Frontiers in Plant Science, 2018)
Heterotrimeric G-proteins are key regulators of a multitude of growth and development pathways in eukaryotes. Along with the conserved G-protein components found in all organisms, plants have certain novel variants with unique architecture, which may be involved in the regulation of plant-specific traits. The higher plant-specific type III (or Class C) Gγ protein, which possesses a large C terminal extension, represented by AGG3 in Arabidopsis, is one such variant of canonical Gγ proteins. The type III Gγ proteins are involved in regulation of many agronomically important traits in plants, including seed yield, organ size regulation, abscisic acid (ABA)-dependent signaling and stress responses, and nitrogen use efficiency. However, the extant data, especially in the monocots, present a relatively complex and sometimes contradictory picture of the regulatory role of these proteins. It remains unclear if the positive traits observed in certain naturally occurring populations are due to the presence of specific allelic variants of the proteins or due to the altered expression of the gene itself. To address these possibilities, we have overexpressed the Arabidopsis AGG3 gene in the model monocot Setaria viridis and systematically evaluated its role in conferring agriculturally relevant phenotypes. Our data show that AtAGG3 is indeed functional in Setaria and suggest that a subset of the traits affected by the type III Gγ proteins are indeed positively correlated with the gene expression level, while others might have more complex, allele specific regulation.